SCIENCE OF UPBRINGING BY LEONAS JOVAIŠA: SYNERGY OF FUNDAMENTALITY AND INNOVATION - Aramavičiūtė, Vanda; Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2010)
The article aims to substantiate the topicality of upbringing and its role in the process of personality education and development. Taking into account the controversial influence of globalisation and post- modernism on contemporary individual‘s values, identity and relations, more focus is laid on education and development of spirituality of an individual and the society as well as on improvement of upbringing as a functional aspect of education, which presupposes coping with outcomes of spiritual crisis. Pursuing this goal, the article summarises the attitude of Leonas Jovai a, a creator of fundamentals of hodegetics, to the science of upbringing. In the context of fundamentality and innovation discourse, its main ideas related to the definition of the purpose, trend and particularity of separate structural components of the process of upbringing are actualised. Following the latest scientific literature and documents of education policy, it is proved that innovation of upbringing goals, modernity of fundamentals and principles of upbringing, integrity of upbringing content and adequacy of means and methods of upbringing declared by Leonas Jovai a have a considerable significance making upbringing more efficient in the context of modern globalisation challenges. The revelation of human origin, as a fundamental component of upbringing, and determination of the place of upbringing in the holistic system of education also receive attention of researchers and theoreticians.